Ramex : a sequence mining algorithm using poly-trees - Cavique, Luís (2015)
Sequence mining combines the discovery of frequent itemsets and the order they appear in. Most of the sequence pattern discovery techniques present some handicaps like the generation of a huge number of rules and the lack of scalability. In this work the proposed algorithm concerns the analysis of the whole rather than the parts, thus providing a holistic view of the sequences. The algorithm analyzes event logs and allows a non-expert user to understand the sequences using a poly-tree visualization. The scalability associated with condensed data structures, which shrink the data without losing information, allows dealing with the Big Data challenge. Ramex was implemented in different scenarios.